1951
DOI: 10.6028/jres.047.059
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries of Zeeman patterns and g-Values for neutral manganese

Abstract: Spectrograms of manganese made a t the Massachusetts In stitute of Technology with fi elds in excess of 84,000 oersteds show many Jines that exhibi t various degrees of di stortion in both the posi ti ons and the intensities of the magnetic components. The in terpretation of these asymmetric patterns has bee n made by t he approximate theory of t he partial PaschenBack effect. The g-values that have been derived fo r several energy levels of Mn I are found to con form , in most cases, with t ho e req uired for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1954
1954
1964
1964

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…These distortions in the case of z6normalF° and z6normalF° levels were ascribed to repulsions between magnetic levels with equal M -values, belonging to adjacent levels of a spectral term, and it was shown that the theory of partial Paschen-Back effects provides a simple rule for obtaining correct g -values in spite of asymmetries in Zeeman patterns. This was elaborated by Catalán [24] who discussed in detail a dozen distorted patterns and concluded that the experimental g -values agreed with those predicted for LS coupling by Landé [7]. Finally, Espinosa [25, 26], in connection with his doctoral thesis, made a complete theoretical interpretation of the very complex Paschen-Back patterns of the z 6 P°— e 6 D and a 6 S— z 6 P° multiplets of Mn I.…”
Section: Methodsmentioning
confidence: 80%
See 3 more Smart Citations
“…These distortions in the case of z6normalF° and z6normalF° levels were ascribed to repulsions between magnetic levels with equal M -values, belonging to adjacent levels of a spectral term, and it was shown that the theory of partial Paschen-Back effects provides a simple rule for obtaining correct g -values in spite of asymmetries in Zeeman patterns. This was elaborated by Catalán [24] who discussed in detail a dozen distorted patterns and concluded that the experimental g -values agreed with those predicted for LS coupling by Landé [7]. Finally, Espinosa [25, 26], in connection with his doctoral thesis, made a complete theoretical interpretation of the very complex Paschen-Back patterns of the z 6 P°— e 6 D and a 6 S— z 6 P° multiplets of Mn I.…”
Section: Methodsmentioning
confidence: 80%
“…The Zeeman data were most helpful in this analysis of Mn I; they have confirmed our interpretation almost completely and have permitted the designation of many terms belonging to the doublet system which was the most difficult to establish. The available Zeeman data for Mn I [6, 21, 23, 24, 27, 28, 29] prove that most of the levels arising from low-energy configurations ( d 5 s 2 , d 5 s , d 5 sp, d 6 p ) exhibit a remarkably pure LS coupling of electrons, and their g -factors are usually identical with the theoretical Landé values, within the error of measurement. Some of the upper levels of both the even and the odd configurations present anomalous g -values that may be explained by intermediate coupling or by incorrect grouping of levels in designated terms.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…There have not been any recent observations of Zeeman effect, but a number of important papers based mainly on prewar investigations have been published: measurements of the Zeeman effect in manganese I from 2460 to 4825 A. (26), asymmetries of Zeeman patterns and y-values in manganese I (25), measurement of nearly 1000 patterns in rhenium spectra (93), a second paper on Zeeman effect and structure in tantalum 1 (11), measurement of Zeeman patterns for 540 ruthenium spark lines (94) photographed in 1940, Zeeman effects in four spectra of tellurium (53) from spectrograms made in 1936, Zeeman effect in chromium I (73) and chromium II (74), and first Zeeman data for dysprosium II (13) observed in 1940.…”
Section: Zeeman Effectmentioning
confidence: 99%